Kekerasan Terhadap Anak: Tantangan Pendidikan - Salabi, Ahmad (IAIN Antasari Banjarmasin, 2015)
Children are the next generations who have strategic roles on ensuring our nationâsÂ existence. To accomplish it, children need to grow and develop naturally. On the otherÂ side, not all of the need can be accomplished; there is still much violence happen on childÂ directed by an adult. There are many cases unveiled because of assumption that is notÂ violence. Even in some society, child abuse is assumed as common because it constituteÂ as cultural norms penalizing child. Islamic education concept is not just an effort toÂ educate intellectually, but it is go with Islamic concept on human and his existence.Â Therefore, Islamic education as social norms is related with Islam concept on humanÂ existence. Islamic education sought to increase understanding and awareness on humanÂ equality in the sight of God. Things that make a difference are his or her devoutness.Â Islamic education is an effort to direct deliberately children development on Islamic values.